Smart hybrid AC/DC distribution network - part I - Ng, Elaine (Nanyang Technological University, 2022)
With the increase of DC inherent loads and renewable energy sources such as solar energy generated from photovoltaic (PV) panels and wind energy generated from wind turbines, the conventional AC distribution system is no longer as efficient and cost effective as it used to be. This is due to the increase of power electronic converter that is used to convert AC power to DC power, and vice versa. In this report, we will study and compare the efficiency and cost of single AC and DC distribution system, and hybrid AC/DC distribution system. With the information found and calculation done, we will then conclude if the AC/DC hybrid distribution system is the most efficient and cost effective when compared with single AC distribution system and DC distribution system.